Assessment of intestinal immunity development in juvenile tiger grouper, Epinephelus fuscoguttatus (Forsskal, 1775) following oral exposure to Bioencapsulated vibriosis vaccine - Nawi, Mohd Firdaus (2017)
Vibriosis outbreaks have been reported in cultured groupers in several countries including Malaysia. Several species of Vibrio were isolated from the infected fish such as Vibrio parahaemolyticus, V. alginolyticus, V. vulnificus and V. carchariae. In Malaysia, the major causative agent of vibriosis is V. alginolyticus and the disease can affect all growth stages of groupers, although juvenile stage is more susceptible. Recent study indicated the intestinal tract is the major portal of entry of V. alginolyticus rather than the gill or skin. Study was conducted to investigate the intestinal immunomorphology development as well as the mucosal immunity of normal juvenile tiger groupers, Epinephelus fuscoguttatus and followed by a study on the immune response following oral adminstrations of bioencapsulated vibriosis vaccine. At the start of the experiment, sixty juvenile tiger groupers obtained from Fisheries Research Institute (FRI) Tg. Demong were euthanized by an overdose of Ethyl 3-aminobenzoate methanesulfonate before the entire intestine was removed and was separated into the anterior, mid and posterior portions. The samples were fixed in 10% buffered formaldehyde for at least 24 h and subjected to histological examinations. The results revealed that the intestinal mucosal immunity in juvenile tiger grouper existed as early as 30 days old, and every region of the intestine has different role either in food absorption or in immunity. However, it was clear that there was a gradual change in function of the intestinal regions from major nutrient absorption function in the anterior intestine to intermediate absorption and immunity functions in the mid intestine to the mainly immunity function in the posterior intestine. Following the immunomorphology study on normal juvenile tiger groupers, the humoral components of the mucosal immunity of normal juvenile tiger groupers were accessed to complete the investigation. Similar number of juvenile tiger grouper as previous experiment were used. Body mucus samples were obtained by gentle scraping of the body surface with sterile plastic scraper involving an area of approximately 2cm in length. After that, the fish were slaughtered and intestinal sample were obtained. Then, all the samples were subjected to lysozyme assay, alkaline phosphatase assay and enzyme-linked immunosorbent assay (ELISA). This assessment study indicated that lysozyme, alkaline phosphatase and natural IgM antibody could be detected as early as in 30 days old and increased parallel with the increasing age of the fish. These findings also demonstrated that every immune substance has its own localize area as manifested by high activities or concentrations. Highest activity of lysozyme was detected in the intestine, especially the posterior and mid regions, while highest level of alkaline phosphatase was detected in the anterior intestine. Highest concentration of natural IgM was detected in the posterior intestine followed by the body mucus. Since all of the important immune substances existed as early as 30 days old juvenile age, it was suggested that vaccination programcould be started at that particular age or earlier.Based on the results of the assessment study, it was decided that administration of the vaccine to the juvenile tiger groupers could be done as early as 15 days old. Bioencapsulated vibriosis vaccine were fed to the juvenile tiger grouper twice; first administration that using bioencapsulated rotifer (Brachionus plicatilis) at 15 days old and followed by booster at 30 days old using the bioencapsulated Artemia. The bioencapsulated vibriosis vaccine was prepared by soaking the rotifer and artemia in sterile sea water containing 3.4 x 109 CFU/mL formalin-killed V. alginolyticus for 2 hours. This vaccination study revealed that oral administrations of bioencapsulated vaccine to 15-day old tiger grouper were able to stimulate short-term innate immunity that lasted 15 days but was able to provide humoral protection for 60 days in the body mucus and more than 105 days in the intestines. Therefore, oral administrations of bioencapsulated vibriosis vaccine into 15 days old tiger groupers followed by booster at 30 days old were able to protect the juvenile tiger groupers for a period of 105 days until they reach 120 days old. The last investigation was conducted to determine the intestinal immunomorphology responses following oral administrations of bioencapsulated vibriosis vaccine. This findings revealed that the oral administrations of bioencapsulated vibriosis vaccine into 15 days old and followed by booster dose at 30 days old juvenile tiger groupers are able to trigger the proliferation and movement of important immune related cells such as goblet cells, lymphoid cells and plasma cells for a period of 3 months, between 30 and 120 days old. The study also demonstrated that the vaccination did not caused changes in the morphology of the intestine as observed in the length and numbers of villi. Thus, it is suggested that oral vaccination of juvenile tiger groupers with bioencapsulated vibriosis vaccine could be given as early as 15 days old and followed by booster at 30 days old to provide protection for the entire hatchery stage.